Parental consanguinity and congenital heart defects in Afghan children with Down's syndrome - Abdul Muhib sharifi; S. Najmuddin Jalal; M. Sharif Sediqi; M. Akbar Ibrahimi; A. Wali Sharifi (Indonesian Pediatric Society, 2021)
Abstract Background: It seems that parents' consanguinity status effects the pattern of congenital heart defects (CHDs). In this study the CHD pattern in children with Down's syndrome (DS) was determined in Afghanistan's children population with a high consanguineous marriage rate and compared with historical cohorts from populations with low prevalence of parental consanguinity. Objective: This analytic cross sectional study aimed to determine the frequency and distribution of CHDs in Afghanistan children with Down's Syndrome as a group in a community with a high consanguineous marriage rate and comparing these with different global studies and populations with low prevalence of consanguinity. Methods: This analytic cross sectional study was conducted in a pediatric teaching hospital in Kabul city - Afghanistan, named Maiwand Hospital. The subjects were all children with DS proven by clinical and cytogenetic study and referred to the pediatric cardiology service from September 2018-September 2020. Parents' consanguinity was documented and 2D echocardiography and Doppler studies were performed by two experienced pediatric cardiologists after physical examination, ECG, and chest X-ray for each patient. Results: During the two-year study period, 120 DS patients were identified, 78 (65%) of whom had CHDs. The prevalence of isolated and multiple CHD in the 78 children with DS were 35% (42 patients) and 30% (36 patients), respectively. Ventricular septal defect (20.5%) and atrial septal defect (15.3%) were the most common isolated defects. The combination of VSD and PDA (20.5%) were the most frequent multiple CHDs. The most common associations of CHD were VSD + PDA (20.5%) and VSD + ASD (10.2%). Consanguinity was found in 69.2 % of all parents. Conclusions: A higher frequency of CHD was documented in DS children from this population with a high consanguineous marriage rate. The frequencies of specific lesions were almost similar to those reported locally and internationally; VSD was the most frequently detected in this study. Interesting was the predominance of left-right shunt lesions and the relative rarity of cyanotic and complex CHD in this DS population. key words: congenital heart disease, atrioventricular septal defect, Down's syndrome, trisomy 21, Afghanistan